Solid state [semiconductors. 1999 technology analysis and forecast]. - Geppert, L.
This article presents a solid-state semiconductor technology analysis and forecast for 1999. The subjects covered include semiconductor technology roadmap targets, silicon-germanium components, silicon-on-insulator ICs, copper IC interconnects and microelectromechanical systems
Keywords: Copper IC interconnects; Microelectromechanical systems; Roadmap targets; Silicon-germanium components; Silicon-on-insulator ICs; Solid-state semiconductor technology; Technology analysis; Technology forecast